Activity and levels of TNF-α, IL-6 and IL-8 in saliva of children and young adults with dental caries: a systematic review and meta-analysis - Mario Alberto Alarcón-Sánchez; Julieta Sarai Becerra-Ruiz; Anna Avetisyan; Artak Heboyan (BMC, 2024)
Abstract Background Cytokines play an important role in the immunopathogenesis of dental caries. A systematic review and meta-analysis was carried out with the following three objectives: 1)To deepen and discuss through a comprehensive analysis of the literature the effects of dental caries on the activity and levels of TNF-α, IL-6 and IL-8 in saliva of children and young adults, 2)To compare the levels of this cytokines in saliva of the exposure group (moderate-severe dental caries) with the control group (caries-free or mild dental caries), and 3)To determine whether the levels of these cytokines could be used as a complementary clinical diagnostic tool to assess the severity of dental caries. Methods The protocol followed PRISMA and Cochrane guidelines and was registered in the Open Science Framework (OSF): https://doi.org/10.17605/OSF.IO/MF74V . A digital search was performed in PubMed/MEDLINE, Cochrane, Scopus, and Google Schoolar databases from February 15th, 2012, to January 13th, 2024. The methodological validity of the selected studies was assessed using Joanna Briggs Institute (JBI) tool. A meta-analysis was performed using a random-effects model to evaluate the association between dental caries/health, and the concentration of TNF-α, IL-6 and IL-8. Results The search strategy provided a total of 126 articles, of which 15 investigations met the inclusion criteria. The total number of patients studied was 1,148, of which 743 represented the case/exposure group, and 405 represented the control group. The age of the patients ranged from 3 to 25 years. IL-6 was the most prevalent cytokine in the saliva of children and young adults with active dental caries. The meta-analysis revealed that there are significant differences between the levels of IL-6 and TNF-α in saliva of children with active dental caries compared to their control groups. Conclusions The findings suggest that IL-6 and TNF-α levels may have potential as complementary biomarkers for assessing dental caries severity. However, further research is needed to validate these findings in larger and more diverse populations before clinical application.